The phenomenological senses of truth in the 6th Logical Investigation - Silva da Rocha, João Marcelo (Sofia, 2024)
This paper aims to present and analyze the different meanings of the concept of ’truth’ outlined by Edmund Husserl in the 6th Logical Investigation. Initially, it addresses the traditional conception of truth as correspondence in its most fundamental aspects. Next, it examines how this idea of adequation, phenomenologically reinterpreted in light of the intentional structure of fulfillment, guides Husserl’s reflection on the concept of evidence, and thus, how this analysis leads to the thematization of the concept of truth, since Husserl defines it as the objective correlate of evidence. This brings us to the core of the investigation: a characterization and discussion of the four senses of truth enumerated by Husserl in paragraph 39 of the 6th Logical Investigation. Finally, some general aspects that articulate these four senses are highlighted, with special emphasis on the primacy of the sense of truth as "being true" in relation to the other phenomenological senses of the concept presented Keywords: Husserl. Truth. Evidence. Concordance. Adequation.